Participação cidadã e poder legislativo estadual: estudo da influência do cidadão na proposição de leis por intermédio do portal da Assembleia Legislativa do Estado de Minas Gerais - Ladinho Júnior, Giovani da Silva (2019)
This paper analyzes the participation of citizens with the legislative branch in sending suggestions of bills, through a specific electronic channel. Therefore, the main objective is to study the influence of citizens in proposing laws through the website of the Legislative Assembly of Minas Gerais - ALMG. The research investigates the participation space of the citizen called "Participe", destined to send suggestions of bills in the portal of the ALMG and analyzes the referral of these suggestions in order to verify and classify those that were accepted and not accepted, in relation the demands of the citizens. The study presupposes that in political representation, in modern representative regimes, there must be some agreement or alignment between the decisions of representatives of legislative houses and the wishes of those they represent. To this end, information and communication technologies can contribute to the traditional approach of public management, creating spaces of communication that stimulate democracy and popular participation, since they provide tools that bring this dialogue closer to the public power. The methodology used was exploratory, with a qualitative and quantitative approach, based on the bibliographic review about the central themes of the research and interviews, as well as a documentary survey and analysis of the suggestions of draft Laws included in the electronic portal of ALMG, in the period between 2011 and 2017. The study showed that the ALMG portal receives the citizens' suggestions on a primary basis and that less than 10% (ten percent) of them are referred to ALMG committees. None of the 964 suggestions analyzed in this study was converted into law. The results reveal a low level of influence of citizens in proposing laws suggested through the portal of the Legislative Assembly of Minas Gerais - ALMG. In the end concluded that, although the use of information and communication technologies represents a good way to increase popular participation, there are difficulties on the part of citizens and on the part of the legislature to make popular participation more effective.